MODELLING OF THE SEMI-DETACHED BINARY STAR WZ CORVI - Virnina, N. A.; Zola, S.; Krajci, T. (Одеські астрономічні публікації, 2012)
We present results from modeling of multicolor light curves of the semi-detached, algol- type binary system WZ Corvi. We analyzed V R data gathered in 2010 and new BV RcIc observations collected in 2012. Two models for WZ Crv are considered: the rst was derived under the assumption that the temperature of the primary component, having the dominant contribution to total system light, corresponds to spectral type F7, and the second model, in which the temperature of the secondary was estimated from the colors observed at the at bottom of the primary minimum. The new set of observations shows almost no dierence in maxima heights, obvious in the earlier, 2010 data. However, primary minimum in V and R is deeper than in the 2010 light curve. We explain the variable shape of the system light curve as spot(s) present on primary or secondary component(s) due to their magnetic activity. Based on the derived solutions, we calculate relative physical (assuming the primary component to be a Main Sequence star) parameters of WZ Crv for both models.